PENGARUH PERLAKUAN HIDROTERMAL TERHADAP MORFOLOGI, SIFAT OPTIK DAN SIFAT LISTRIK LAPISAN TIPIS NANORODS ZNO - Lalu Suhaimi (National Research and Innovation Agency (BRIN), 2020)
Zinc oxide nanorods (ZnO NRs) is a semiconductor material that has been widely applied in various fields. In this research, ZnO NRs were successfully grown on ITO substrates by chemichal bath deposition (CBD) method. The process begins with making a seed solution using an ecimolar mixture of Zn-Nitrate and hexamethylentetramine (HMTA) at 00C for one hour with 0.015 M concentration. Furthermore, making a layer of seeds using spin coating technique. ZnO NRs were grown using the CBD method at 900C for three hours then treated with variations which are hydrothermal method treatment and non-hydrothermal method treatment at 1500C for three hours. Samples were given characterization treatment using SEM, XRD, UV-Vis and four-point probe. SEM results showed that hydrothermal treatment was able to increase the coverage of nanorods on the substrate to be more prevelently and was able to increase the vertical structure of the nanorods. The results of XRD analysis showed that samples given hydrothermal treatment experienced an increase in the crystallite size. The amount of crystallite size in the sample treated with variation of non-hydrothermal treatment and hydrothermal treatment was 71, 198 and 165.696 nm. Hydrothermal treatment of nanorods samples decreased the sample diameter from 288,252 nm to 125,824 nm. The transmittance value of the samples decreased in the presence of hydrothermal treatment which is 56.53% to 38.67%. The hydrothermal treatment was able to reduce the energy bandgap (Eg) of the sample, while the sample of non-hydrothermal treatment showed value of the Eg was 3.22 eV. Meanwhile, the value of Eg after hydrothermal treatment was 3.17 eV. The resistivity value of ZnO NRs with hydrothermal treatment was 0.833 x 10-4 Ωcm, while the resistivity value of non-hydrothermal treatment was 1.126 x 10-4 Ωcm. Key words: zinc-oxide nanorods, chemical bath deposition, hydro-thermal